PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, FINANCIAL LEVERAGE, KLASIFIKASI KAP DAN LIKUIDITAS TERHADAP PRAKTIK PERATAAN LABA - Harris Prasetya; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2013)
The aimed of this study was to examine the influence of size of company, profitability, financialleverage, public accountant office classification , and liquidity toward income smoothing practiceamong list manufacture companies at Indonesia Stock Exchange on period 2007-2010. The factorsbeing examined were size of company, profitability, financial leverage, public accountant officeclassification, and liquidity. Index Eckel is used to determine the income smoothing practice Thestudy was using 80 manufacture company listed in Indonesia Stock Exchange, with a periodbetween 2007-2010. The hypothesis were twsted using binary logistic regression to examine theinfluence size of the company, profitability, financial leverage, public accountant officeclassification, and liquidity toward income smoothing practice.The result of this study showed thatsome of the listed manufacturers on Indonesia Stock Exchange committed income smoothingpractice. Financial leverage, and liquidity has significant influence to income smoothing. Size ofthe company, profitability, and public accountant office classification did not have influence toincome smoothing.